Model Pemberdayaan Masyarakat melalui Pengolahan Kopi di Desa Mandiri Energi - Yohanes Aris Purwanto; Kukuh Murtilaksono; Sri Malahayati Yusuf (Institut Pertanian Bogor, 2015)
Development of energy self-sufficient village based on the local resources is purposed to reduce the poverty, to create the job opportunities as well as to substitute the fossil fuels. Energy self-sufficient village is also as sociated with the development of the productive economy. For the areas closed to national park, the development of the productive economy is important because it can reduce community activities for reaching the forest. Lebakpicung is energy self-sufficient village based on microhydro. This village has potency on coffee production. However, only dried coffee beans are produced from this village. The purpose of this community empowerment activity in Energy self-sufficient village was to utilize idle electricity from microhydro during day time as energy resource for coffee processing. This activity was carried out through training activity on the use of coffee processing machinery and packaging technology. The training participants were the community members who has activity on coffee processing.